Well-log Analysis of Shale Gas Reservoirs - Rezaee, Reza; Iqbal, Atif (2022)
Well-logs provide continuous information about rocks and their pore fluid properties. Typical well-logs such as gamma-ray, density, neutron, sonic, and resistivity logs have been traditionally used to estimate shale volume, porosity, lithology, and fluid saturation in conventional oil and gas exploration, where shale formations are treated as hydrocarbon sources rocks and sandstone and carbonate formations are reservoir rocks for the migrated oil and gas. However, well-log interpretations for unconventional shale plays, in which shale formations are targeted as self-sourced reservoir rocks, do not follow the same methodologies used for conventional sandstone and carbonate reservoirs. This is due to the complex nature and additional parameters that are required to be estimated for shale reservoirs. Moreover, well-log methodologies for reservoir-fluid characterization have been traditionally advanced and calibrated for sandstone and carbonate rocks. Nevertheless, certain novel concepts and emerging procedures attempt to utilize well-logs for the evaluation of shale reservoirs including their organic richness, porosities, water saturation, gas volumes, and geomechanical properties.